Faktor-Faktor yang Mempengaruhi Pendapatan Pengrajin pada Industri Kerajinan Bambu di Desa Belega Kabupaten Gianyar - Sasmitha, Ni Putu Ria; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This study aimed to determine the effect of simultaneous and partial working hours, gender, age and working capital to revenue bamboo craftsmen in the village Belega Gianyar regency. The population in this study are all bamboo craftsmen in the village Belega Gianyar regency. The samples used are as many as 80 bamboo craftsmen using sampling methods ie Non Probability Sampling. The analysis technique used is multiple linear regression analysis. The analysis showed working hours, gender, age and working capital simultaneously significant effect on the income of bamboo craftsmen in the village Belega Gianyar regency. Partially working hours and working capital have positive and significant impact on the income of craftsmen in bamboo handicraft industry in the village Belega Gianyar regency. Partially gender variable effect on revenue craftsmen in bamboo handicraft industry in the village Belega Gianyar regency. There are differences in income earned by male workers and female. Meanwhile, partially age have  significant negative effect on revenues in the industry bamboo handicraft artisans in the village Belega Gianyar regency.
Keywords: working hours; gender; age; capital; income